Fresh Inroad into The Emancipation of Women - Dr. Vasudha Maitre (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Abstract: K.R. Meera is a renowned Indian author whose works explore complex societal issues, with a particular focus on women’s struggles within patriarchal structures. Her narratives often center around feminist themes, questioning the conventional roles women are expected to play and the emotional, psychological, and social conflicts they endure. This paper delves into Meera’s notable works such as ‘Aarachar’ (Hangwoman), ‘Meera Sadhu’ (The Poison of Love), ‘Yudasinte Suvishesham’ (The Gospel of Yudas), and ‘Moha Manja’ (Yellow Is The Colour of Longing), highlighting how these stories reflect deep societal critiques and intense emotional landscapes. Through powerful female protagonists, Meera portrays the inner struggles of women against identity loss, betrayal, and oppression while offering a critique of societal norms. Her writing style, marked by metaphor, symbolism, and poetic language, contributes significantly to feminist thought and contemporary Malayalam literature. Meera’s exploration of themes such as love, loss, power dynamics, and societal expectations makes her a prominent voice in modern Indian literature.